PENCEGAHAN TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA BANTUAN SOSIAL DALAM PENANGANAN COVID-19 (Studi Kasus Putusan Nomor: 29/Pid.Sus-TPK/2021/PN.Jkt.Pst) - Idham Chalid (Universitas Kapuas, 2023)
Corruption that occurs in the procurement of goods and services (PBJ) is included in the category of extraordinary crimes, not only can harm state finances but also violates the law, social and economic rights of the wider community. A more comprehensive handling of the various problems of criminal acts of corruption in social assistance PBJ is needed in handling Covid-19. This is the background for the authors to conduct research with a normative legal research approach. Conduct analysis related to the implementation of PBJ in relation to laws and regulations as well as the opinions of legal experts. This is very important, in order to be able to describe the various causes of criminal acts of corruption and efforts to prevent them. In the author's note regarding the factors causing the criminal act of corruption in PBJ social assistance in handling Covid-19 as in the case of Decision Number: 29/Pid.Sus-Tpk/2021/Pn.Jkt.Pst, there are two (2) important things: subjective factors and objective. Subjective factors, related to weak personal integrity, because of the urge to fulfill the need for